Anti-mullerian hormone (AMH) is associated with natural menopause in a population-based sample: The CARDIA Women's Study. Issue 4 (August 2015) - Nair, Sangeeta; Slaughter, James C.; Terry, James G.; Appiah, Duke; Ebong, Imo; Wang, Erica; Siscovick, David S.; Sternfeld, Barbara; Schreiner, Pamela J.; Lewis, Cora E.; Kabagambe, Edmond K.; Wellons, Melissa F.
Abstract Objective AMH is associated with menopausal timing in several studies. In contrast to prior studies that were restricted to women with regular cycles, our objective was to examine this association in women with either regular or irregular menstrual cycles. Methods CARDIA is a longitudinal, population-based study that recruited adults ages 18–30 when it began in 1985–1986. AMH was measured in serum stored in 2002–2003. Natural menopause was assessed by survey in 2005–2006 and 2010–2011. Results Among 716 premenopausal women, median [25th, 75th] AMH was 0.77 [0.22–2.02] ng/dL at a median age of 42 [39–45] years. Twenty-nine percent of the women (n = 207) reported natural menopause during 9 years of follow up. In fully adjusted discrete-time hazard models, a 0.5 ng/dL AMH decrement was associated with higher risk of menopause (p < 0.001). Hazard ratios varied with time since AMH measurement. The HR (95% CI) for menopause was 8.1 (2.5–26.1) within 0–3 years and 2.3 (1.7–3.3) and 1.6 (1.3–2.1) for 3–6 and 6–9 years, respectively. When restricted to women with regular menses, results were similar (e.g., HR = 6.1; 95% CI: 1.9–20.0 for 0–3 years). Conclusion AMH is independently associated with natural menopause. AMH appears most useful in identifying women at risk of menopause in the near future (within 3 years of AMH measurement).